What Matters When? Social and Dimensional Comparisons in the Context of University Major Choice. (May 2021) - von Keyserlingk, Luise; Dicke, Anna-Lena; Becker, Michael; Eccles, Jacquelynne S.
Students compare their achievement to different standards in order to evaluate their ability. We built on the theoretical frameworks of situated expectancy-value theory, dimensional comparison theory, and the big-fish-little-pond effect literature to examine the role of social and dimensional comparisons for ability self-concept and subjective task value (STV) in secondary school and university major choice. We used two German longitudinal data sets from different cohorts with data collection in 12th grade and 2 years after high school graduation (Study 1: N = 2, 207, Study 2: N = 1, 710). Dimensional and social comparisons predicted students' self-concept and domain-specific STV in school: Individual achievement was positively related to ability self-concept and STV in the corresponding domain and negatively related in the noncorresponding domain. School-level mean achievement was negatively related to ability self-concept and STV in the corresponding domain. Dimensional comparisons were directly related to university major choice, social comparisons were only indirectly related.